Analisis Perhitungan Biaya Untuk Menentukan Harga Jual Jasa Pemain Pengganti Game Online - Masiakh , Johan Arista Rapha El; Restuti, Mitha Dwi (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2024)
Cost is important information for organization to determine the selling prices and profit targets. This research aims to explore the cost calculation for online game substitute services in order to determine the selling price. This research focuses on cost calculations and the methods used to determine the selling price. The research method used is direct interviews to online game substitute services providers. The providers taking 3 (three) genres, including MOBA, RPG, and FPS. The results show that the method used to calculate costs is relatively simple and no special calculations. The selling price offered to consumers is more based on the market price and the cost calculation is a minor consideration.